Refolding of an integral membrane protein. Denaturation, renaturation, and reconstitution of intact bacteriorhodopsin and two proteolytic fragments. - Huang, K; Bayley, H; Liao, M; London, E; Khorana, H (1981)
The complete denaturation and subsequent renaturation and reconstitution of a polytopic integral membrane protein are demonstrated. Delipidated bacteriorhodopsin (Huang, K.-S., Bayley, H., and Khorana, H. G. (1980) Proc. Natl. Acad. Sci. U. S. A. 77, 323-327) is completely denatured when transferred into 88% formic acid or anhydrous trifluoroacetic acid as shown by NMR and circular dichroism spectroscopy. When ethanol is added to a solution of the denatured protein, helical structure is largely reformed. After neutralization of the acid with ammonia and dialysis against a solution of sodium dodecyl sulfate a substantial amount of this structure is retained. Complete renaturation, characterized by the formation of the chromophore, occurs when phospholipids, cholate, and retinal are added to the sodium dodecyl sulfate solution of the protein. After dialysis of the solution to remove the detergents, the bacteriorhodopsin assembles into vesicles that are fully active in light-driven proton translocation. We also show that two chymotryptic fragments of bacteriorhodopsin (residues 1-71 and 72-248), separated under denaturing conditions, can be made to reassociate and form active vesicles with phospholipids.